COVID-19-Related Severe Hypercoagulability in Patients Admitted to Intensive Care Unit for Acute Respiratory Failure - Spiezia, Luca; Boscolo, Annalisa; Poletto, Francesco; Cerruti, Lorenzo; Tiberio, Ivo; Campello, Elena; Navalesi, Paolo; Simioni, Paolo (Thrombosis and Haemostasis, 2020)
In late December 2019 an outbreak of a novel coronavirus (SARS-CoV-2) causing severe pneumonia (COVID-19) was reported in Wuhan, Hubei Province, China. A common finding in most COVID-19 patients is high D-dimer levels which are associated with a worse prognosis. We aimed to evaluate coagulation abnormalities via traditional tests and whole blood thromboelastometry profiles in a group of 22 (mean age 67 ± 8 years, M:F 20:2) consecutive patients admitted to the Intensive Care Unit of Padova University Hospital for acute respiratory failure due to COVID-19. Cases showed significantly higher fibrinogen and D-dimer plasma levels versus healthy controls (p < 0.0001 in both comparisons). Interestingly enough, markedly hypercoagulable thromboelastometry profiles were observed in COVID-19 patients, as reflected by shorter Clot Formation Time (CFT) in INTEM (p = 0.0002) and EXTEM (p = 0.01) and higher Maximum Clot Firmness (MCF) in INTEM, EXTEM and FIBTEM (p < 0.001 in all comparisons). In conclusion, COVID-19 patients with acute respiratory failure present a severe hypercoagulability rather than consumptive coagulopathy. Fibrin formation and polymerization may predispose to thrombosis and correlate with a worse outcome.
Keywords: thromboelastometry; fibrinogen/fibrin; thrombotic complications